Turn. Washington's spies. Season 3 [videorecording (DVD)] - Silverstein, Craig; Bell, Jamie, 1986-; Numrich, Seth; Lind, Heather; Henshall, Daniel, 1983-; McNally, Kevin; Kahn, Ian, 1972-; Yeoman, Owain, 1978-; Rose, Alexander, 1971- (2016)
It takes viewers into the stirring and treacherous world of the Revolutionary War and America's first spy ring. This season returns with an epic ten-episode season that builds towards one of the most notorious moments in American history, the treasonous defection of Benedict Arnold. Behind enemy lines on Long Island, Abe Woodhull is a spy for the Patriots, reporting directly to George Washington. Embedded within the Continental Army, Benedict Arnold is seduced to become an informant.